The Application of Crossword Puzzle Therapy (CPT) to Improve Cognitive Function in Older Adults in Griya Lansia Garut: A Case Study - Pataya, Amalla; Witdiawati, Witdiawati; Sari, Sheizi Prista (Universitas Padjadjaran, 2025)
Introduction: Older adults are an age group that is vulnerable to a decline in cognitive function as they age. One of the efforts to slow down the process is through the provision of fun and structured cognitive stimulation, such as crossword puzzle games or Crossword Puzzle Therapy (CPT). Objective: : To determine the effectiveness ofthe application of CPT on improving cognitive function in older adults who experience mild cognitive function impairment. Methods: This study used a case study method with a nursing approach to a 74-year-old older adult with mild cognitive function impairment at Griya Lansia Garut. Cognitive function was measured using a questionnaire with the intervention given was Crossword Puzzle Therapy (CPT) for six times in ten days. Results: There was an increase in cognitive scores (from 18 to 21) before and after the intervention, especially in aspects of orientation and short-term memory. Clients can perform CPT exercises with assistance and only in the easiest CPT level. Conclusion: This study shows that CPT intervention can be an effective alternative nonpharmacological therapy to stimulate and improve cognitive function in older adults. A longer time and increase the sample size with various characteristics to determine the broader effectiveness of this intervention are recommended. The activity should begin with a low level of difficulty and be tailored to the individual’s ability in order to achieve more optimal outcomes. Keywords: Cognitive Function, Crossword Puzzle Therapy (CPT), Older Adult